2019
DOI: 10.1210/jc.2018-02808
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of a Single Session of RFA for Benign Thyroid Nodules: A Longitudinal 5-Year Observational Study

Abstract: Context Radiofrequency ablation (RFA) of benign thyroid nodules has been gaining consensus. However, no solid information on its long-term efficacy is available. Objective To analyze the long-term results of single-session RFA. Design Retrospective longitudinal observational study. Setting Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 30 publications
6
88
1
5
Order By: Relevance
“…It should be noted that few patients reached the 4 or 5-year follow-up milestone (57 and 6, respectively), and two RF sessions were necessary for 20% of the patients, with a mean time to additional RF ablation of 8.5 ± 7.5 months after the initial RF ablation. Another Italian single-center study evaluating 215 patients treated with only one session, found a mean 5-year VRR of 67% [10]. For L, studies with a 3-to 6-year follow-up, showed a reduction rate of approximately 50-60%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that few patients reached the 4 or 5-year follow-up milestone (57 and 6, respectively), and two RF sessions were necessary for 20% of the patients, with a mean time to additional RF ablation of 8.5 ± 7.5 months after the initial RF ablation. Another Italian single-center study evaluating 215 patients treated with only one session, found a mean 5-year VRR of 67% [10]. For L, studies with a 3-to 6-year follow-up, showed a reduction rate of approximately 50-60%.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, thermal treatments such as radiofrequency (RF) and laser (L) therapy have shown to be a reliable alternative to surgery as a result of their ability to induce a significant reduction of benign nodules that, in most cases, is sustained long term [6][7][8]. In 5-30% of nodules, two unfavorable outcomes have been observed: a volume reduction rate (VRR) < 50% after the first thermal ablation and progressive regrowth [9][10][11][12][13]. These two outcomes represent two sides of the same coin, as it has been shown that nodules, which decrease to a lesser extent, are those which are prone to regrowth in 4-5 years [14].…”
Section: Introductionmentioning
confidence: 99%
“…RFA is an effective TA treatment for thyroid nodules [54,55]. Mean volume reduction in randomized controlled trials, which did not always differentiate complex from solid nodules, ranged from 69 to 78% at 12-month follow-up [56,57], and a 5-year retrospective study demonstrated long-term clinical efficacy with a median 67% volume reduction [58]. In the previously quoted meta-analysis, RFA was associated with a 68, 75, and 87% mean VRR at 6, 12, and 24 months, respectively [49].…”
Section: Radiofrequencymentioning
confidence: 99%
“…As a general rule, the smaller the treated nodule the higher the volume reduction (78-82% in ≤10to 12-mL nodules vs. 62-65% in > 20-to 30-mL nodules) [56,57]. As tissue structure affects the alternating current flow, compact tissues are more resistant than soft tissues and, as for LTA, spongiform and mixed nodules respond better to RFA than solid lesions [58,59]. RFA treatment has been shown to ameliorate pressure as well as cosmetic symptom scores [58,60].…”
Section: Radiofrequencymentioning
confidence: 99%
See 1 more Smart Citation